"Journal: 100 Years / Keysone National Powder Company, Catalog 1912" - Robert Hopler (International Society of Explosives Engineers, 2013)
THE KEYSTONE NATIONAL POWDER COMPANY is an Independent organization, incorporated under the laws of the State of Pennsylvania. It has three dynamite mills near Emporium, Pa., with a daily capacity of 165,000 pounds. It maintains branch offices in practically all the largest cities east of the Rocky Mountains, and has distributing magazines located in every section where there is a demand for high explosives, with facilities for wagon deliveries. Our mills are all of modern type and are equipped with the most improved machinery for the manufacture of high explosives. The efficiency of our laboratory in conjunction with the high class of labor employed, has enabled us to put on the market an explosive, the quality of which is the result of extensive research and scientific knowledge. Our modern and complete equipment for harbor and railroad transportation insures our patrons of prompt deliveries, which is an essential feature particularly to contractors and those whose facilities for storage are limited.